1984
DOI: 10.1007/bf00056766
|View full text |Cite
|
Sign up to set email alerts
|

Triploidy in Gallus domesticus embryos, hatchlings and adult intersex chickens

Abstract: The frequency of triploidy was studied in early chicken embryos and hatchlings and in adult chickens which showed symptoms of intersexuality at an early age. The incidence of triploid embryos in the strain involved was not very high (0.6%), but it appeared to increase significantly when embryos were studied from eggs laid by very young hens (4.4%). Among the hatchlings screened only one single triploid individual was found (0.2%). The majority of the adults suspected of intersexuality proved to be triploid wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Triploidy occurs in up to 3.3% of chicken embryos and is a known cause of embryo mortality in birds [Forstmeier and Ellegren, 2010]. In domestic chickens, spontaneous triploidy is well documented [de Boer et al, 1984;Bonaminio and Fechheimer, 1993] with viable, but infertile ZZZ and ZZW gonosomal types. Lin et al [1995] reported that ZZZ birds have irregular meiosis and produce abnormal spermatozoa, but the behavior of chromosomes during meiosis was not described.…”
Section: The Effects Of Abnormal Chromosome Complements On Avian Meiosismentioning
confidence: 99%
“…Triploidy occurs in up to 3.3% of chicken embryos and is a known cause of embryo mortality in birds [Forstmeier and Ellegren, 2010]. In domestic chickens, spontaneous triploidy is well documented [de Boer et al, 1984;Bonaminio and Fechheimer, 1993] with viable, but infertile ZZZ and ZZW gonosomal types. Lin et al [1995] reported that ZZZ birds have irregular meiosis and produce abnormal spermatozoa, but the behavior of chromosomes during meiosis was not described.…”
Section: The Effects Of Abnormal Chromosome Complements On Avian Meiosismentioning
confidence: 99%
“…Two diploid-triploid chickens have been reported pre viously (Abdel-Hameed and Sholfncr. 1971;De Boer et al, 1984), and viable diploid-triploids have been found in turtles (Bickham et al, 1985), fish (Murayama et al, 1986), and mammals, including man (Gra ham et al, 1981) 1973), and mink (Fechheimer et al. 1983).…”
mentioning
confidence: 99%
“…When the incidence of male gonads within a treatment group was too low, this treatment was repeated in another experiment. Karyotyping was performed as described by De Boer et al (1984), using the remaining soft tissues of the embryos. In the experiment in which morphometric measurements were also made, the histology procedure was the same as that described for the in vitro reaggregation culture.…”
Section: In Vitro Organ Culturementioning
confidence: 99%